2014
DOI: 10.1007/s00253-014-5866-5
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae: a potential host for carboxylic acid production from lignocellulosic feedstock?

Abstract: Carboxylic acids are important bulk chemicals that can be used as building blocks for the production of polymers, as acidulants, preservatives and flavour compound or as precursors for the synthesis of pharmaceuticals. Today, their production mainly takes place through catalytic processing of petroleum-based precursors. An appealing alternative would be to produce these compounds from renewable resources, using tailor-made microorganisms. Saccharomyces cerevisiae has already demonstrated its value for bioethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 142 publications
0
13
0
Order By: Relevance
“…109 Annual production of these compounds is as follows (ktons): acetic acid: 10 000; acrylic acid: 4200; 3-hydroxypropionic acid: 3600; adipic acid: 3000; citric acid: 1600; lactic acid: 450; fumaric acid: 200; gluconic acid: 87; itaconic acid: 80; malic acid: 60; glucaric acid: 42; glycolic acid: 40; and succinic acid: 37. Acetic and lactic acids are used as food preservatives.…”
Section: Organic Acidsmentioning
confidence: 99%
“…109 Annual production of these compounds is as follows (ktons): acetic acid: 10 000; acrylic acid: 4200; 3-hydroxypropionic acid: 3600; adipic acid: 3000; citric acid: 1600; lactic acid: 450; fumaric acid: 200; gluconic acid: 87; itaconic acid: 80; malic acid: 60; glucaric acid: 42; glycolic acid: 40; and succinic acid: 37. Acetic and lactic acids are used as food preservatives.…”
Section: Organic Acidsmentioning
confidence: 99%
“…Baker’s yeast, Saccharomyces cerevisiae, can be used for production of a range of different commodity chemicals [1], [44], biofuels [20], [25], [41], bioflavours [8], fine chemicals [45], [46], [54] and pharmaceuticals [17], [53]. It is used as production host for approximately 20% of biopharmaceuticals approved by the Food and Drug Administration (FDA) or by the European Medicines Agency (EMA) [15].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates the importance of a more efficient product exporter. This prominence of examining transport processes, such as substrate uptake and product export, possibly coupled to cellular energetics, for microbial organic acid production was mentioned for various organic acids in different host organisms (Beauprez et al, ; Sandström et al, ; Sauer et al, ). Therefore, an even more powerful succinate exporter and the elimination of residual succinate import activity should be the first new targets, because it has been shown that central metabolism is flexible enough to accommodate large changes in fluxes.…”
Section: Resultsmentioning
confidence: 99%